Encapsulating sheet, display panel, and method for manufacturing display panel

The sealing sheet with a resin composition layer addresses adhesion and air bubble issues in micro LED displays, ensuring easy positioning and improved panel appearance and yield.

JP7619513B1Active Publication Date: 2025-01-22TOYO INK MFG CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2024080203
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-05-16
Publication Date
2025-01-22
Estimated Expiration
2044-05-16

AI Technical Summary

Technical Problem

Conventional sealing sheets for micro LEDs face issues with adhesion to micro-sized LED elements, difficulty in positioning, and the formation of air bubbles due to narrow spacing, leading to poor appearance and low yield in display panels.

Method used

A sealing sheet comprising a first film, a resin composition layer with specific surface roughness, glass transition temperature, and loss tangent, and a second film, designed to facilitate easy positioning and prevent air bubbles by ensuring uniform adhesion and filling around micro LEDs.

Benefits of technology

The sealing sheet effectively prevents adhesion to micro LEDs, allows easy positioning, and minimizes air bubbles, resulting in improved appearance and higher yield in display panels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619513000001_ABST
    Figure 0007619513000001_ABST
Patent Text Reader

Abstract

An object of the present invention is to provide an encapsulating sheet which is unlikely to cause blocking of LED elements, is easy to change the mounting position, is unlikely to cause poor appearance, and is unlikely to cause voids on the bottom surface or corners of a recess. [Solution] A sealing sheet for sealing between light-emitting elements for a display using a plurality of light-emitting elements as a light source, The encapsulating sheet includes a first film, a resin composition layer for forming an encapsulating layer, and a second film arranged in this order, The surface roughness Ra of the resin composition layer on the surface in contact with the first film is 0.02 μm or more, The resin composition layer has a glass transition temperature of 20° C. or higher and a loss tangent (tanδ) at 100° C., which is measured by dynamic viscoelasticity measurement in a torsion mode at a frequency of 1 Hz. 100 ) is 0.2 or more, Sealing sheet.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an encapsulating sheet, and more particularly to an encapsulating sheet including a resin composition layer for encapsulating a micro LED used in a display using a micro LED as a light source, a display panel having a encapsulating layer formed from the resin composition layer, and a method for manufacturing a display panel. [Background technology]

[0002] In recent years, displays have been actively developed using various light-emitting elements in order to achieve higher performance. Specifically, various display specifications are being researched, such as backlit displays using liquid crystal or quantum dots, displays using self-emitting elements such as mini / micro LEDs and organic EL, plasma displays, and electrophoretic displays, and a wide range of uses are being considered, from large display applications such as signage and televisions to small-sized applications such as tablets, personal computers, smartphones, and wearable devices. In particular, the development of displays using LEDs is progressing day by day, and Patent Documents 1 to 4 describe encapsulating sheets for encapsulating multiple LED elements. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2023-12051 A [Patent Document 2] International Publication No. 2021 / 200035 [Patent Document 3] International Publication No. 2021 / 245830 [Patent Document 4] International Publication No. 2022 / 145399 Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, LED elements have become smaller, and the intervals between the LED elements and the substrate are becoming narrower. Conventional encapsulating sheets have excellent heat resistance and ease of handling, but have the following problems: When the encapsulating sheet is placed on the upper surfaces of multiple micro-sized LED elements, even if an attempt is made to change the position, the encapsulating resin composition layer sticks to the upper surfaces of the LED elements, making it difficult to change the position. In addition, when the encapsulating resin composition layer was pressed into the recesses between multiple micro-sized LED elements, it was not possible to sufficiently remove the air between the substrate on which the LED elements were mounted and the encapsulating resin composition layer, and large air bubbles (over 100 μm) remained between the substrate and the encapsulating resin composition layer at the bottom of the recesses between the multiple LED elements, resulting in a very poor appearance when viewed from the substrate side and being one of the causes of low yields.

[0005] An object of the present invention is to provide an encapsulating sheet which is unlikely to cause blocking of LED elements, is easy to change the mounting position, is unlikely to cause poor appearance, and is unlikely to cause voids on the bottom surface or corners of a recess. [Means for solving the problem]

[0006] As a result of extensive research into solving the above problems, the present inventors have arrived at the inventions described in [1] to [8] below. That is, [1]: An encapsulating sheet for sealing between light-emitting elements for a display using a plurality of light-emitting elements as a light source, the encapsulating sheet includes a first film, a resin composition layer for forming a sealing layer, and a second film arranged in this order, the resin composition layer has a surface roughness Ra of 0.02 μm or more on a surface in contact with the first film, the resin composition layer has a glass transition temperature of 20° C. or more, and a loss tangent (tanδ) at 100° C., the glass transition temperature being measured by dynamic viscoelasticity measurement in a torsion mode at a frequency of 1 Hz. 100 ) is 0.2 or more.

[0007] [2]: Loss tangent at 100℃ (tanδ 100) is 2.5 or less. [3]: The encapsulating sheet according to the above [1] or [2], wherein a cut level difference RΔc of a contour curve of the resin composition layer on a surface in contact with the first film is 0.05 to 20 μm. [4]: The loss modulus (G'') at 100°C obtained by dynamic viscoelasticity measurement at a frequency of 1 Hz of the resin composition layer. 100 ) but 5×10 3 Pa~2×10 7 The encapsulating sheet according to any one of the above [1] to [3], [5]: The encapsulating sheet according to any one of the above [1] to [4], wherein the resin composition layer has a thickness Ta of 1 to 100 μm.

[0008] [6]: A display panel having an encapsulating layer made of a resin composition layer of the encapsulating sheet according to any one of [1] to [5] above.

[0009] [7]: A method for manufacturing a display panel, comprising the following steps (1) to (6). (1) A step of preparing an encapsulating sheet according to any one of the above [1] to [5], in which a first film, a resin composition layer for forming an encapsulating layer, and a second film are arranged in this order; (2) preparing an object to be sealed, the object having a plurality of light-emitting elements arranged at intervals on one surface of a substrate; (3) peeling off the first film from the encapsulating sheet to expose the resin composition layer for forming an encapsulating layer; (4) contacting the exposed resin composition layer for forming a sealing layer with the light emitting surfaces of the plurality of light emitting elements; (5) filling spaces between the light-emitting elements with a resin composition layer for forming a sealing layer; (6) Peeling off the second film. Effect of the Invention

[0010] According to the present invention, it is possible to provide an encapsulating sheet which is less likely to cause blocking of LED elements, is easy to change the mounting position, is less likely to cause poor appearance, and is less likely to cause gaps on the bottom surface or corners of a recess. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of a laminate configuration of an encapsulating sheet. [Diagram 2] 1A to 1C are schematic cross-sectional views showing a step of sealing a light-emitting element on a substrate having a light-emitting element thereon. [Diagram 3] FIG. 1 is a cross-sectional view showing an example of a test substrate simulating a micro LED substrate. [Figure 4] FIG. 4 is a schematic cross-sectional view for explaining an image of a cut level difference Rδc of a profile curve. [Diagram 5] FIG. 2 is a schematic diagram for explaining a method for evaluating blocking resistance in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present disclosure will be described in detail below. Note that the embodiment described below is an example of the present disclosure. The present disclosure is not limited to the following embodiment, and includes modified examples that are implemented within the scope of the present disclosure. In this specification, a numerical range specified by using "~" includes the numerical values ​​written before and after "~" as the range of the lower and upper limits. (Meth)acrylic acid refers to acrylic acid and methacrylic acid. In addition, unless otherwise noted, the various components appearing in this specification may each be used independently as one type alone or in combination of two or more types. When two or more types are used in combination, the content is the total value.

[0013] [Form of encapsulating sheet] As shown in Fig. 1, the sealing sheet of the present disclosure has a first film, a resin composition layer, and a second film arranged in this order. A plurality of resin composition layers can be provided. When adopting the three-layer structure shown in Fig. 1, the first film can be laminated after forming the resin composition layer on the second film, or the second film can be laminated after forming the resin composition layer on the first film, and the former manufacturing method is preferred. After or during the production of the encapsulating sheet, the encapsulating sheet is wound around a core in a roll shape to obtain an encapsulating sheet roll. The winding length can be designed depending on the application. From the viewpoint of increasing productivity, it is preferably 50 m or more, and more preferably 100 m or more. From the viewpoint of production yield, the winding length is preferably 10,000 m or less. When the encapsulating sheet is in the form of a roll, it is preferable to provide the first film on the outside of the winding.

[0014] The encapsulating sheet of the present disclosure is used to seal between light-emitting elements for a display using a plurality of light-emitting elements as a light source. The light-emitting element is preferably a micro LED, and the light-emitting color is not particularly limited, but may be, for example, red, green, or blue. The encapsulating sheet of the present disclosure is preferably used to seal a micro LED array in which a large number of elements of the three colors are regularly arranged on a substrate. That is, the encapsulating sheet of the present disclosure is preferably used to seal between a red (R) element and a green (G) element, between a G element and a blue (B) element, between a B element and an R element, or between [R element, G element, and B element] units. The resin composition layer is preferably directly attached to the micro LED to seal it. The micro LED is preferably arranged on a substrate such as, but not limited to, acrylic, urethane, polycarbonate, epoxy, polyimide, glass, paper, cloth, aluminum, ceramic, or polyethylene terephthalate, and has an electrode portion.

[0015] Since the resin composition layer has high conformability to uneven surfaces, it is suitable to use the resin composition layer to conform to the micro LEDs and fill the gaps between the micro LEDs. By filling the gaps between the micro LEDs with the resin composition layer, a sealing layer made of the resin composition layer is formed. The sealing layer has the function of fixing adjacent micro LEDs and preventing them from falling off. In particular, it is more preferable to use the resin composition layer as a sealing layer for a micro LED display panel. Micro LEDs are tiny LED elements (chips) measuring 50μm or less than 100μm. By mounting multiple micro LEDs on a substrate with wiring and circuits, a display is formed that uses multiple optical semiconductor elements as light sources. Micro LEDs are made up of GaAs, GaP, AlGaInP, InGaN or other LED elements, sealing resin to seal them, package substrate, electrodes, etc., and have an operating temperature of 25 to 60°C. An example of a process for forming a sealing layer will be described below with reference to FIG. Although not shown, a step preceding the step (a) shown in FIG. 2 is to prepare an object to be sealed, which has a plurality of micro LEDs arranged at intervals on one surface of a substrate.

[0016] Step (a): Step of placing the encapsulating sheet As shown in FIG. 2(a), the first film is peeled off from the encapsulating sheet to expose the resin composition layer, and then the resin composition layer of the encapsulating sheet is placed on a substrate having multiple micro LEDs so as to directly cover the entire multiple micro LEDs. In this specification, the number of micro LEDs is not particularly limited. In display applications, the number of micro LEDs used is determined by the display size and the number of pixels. The size of the micro LED is less than 100μm in thickness and 40,000μm in plan view area. 2 The following is preferable: a thickness of 50 μm or less, and a planar area of ​​10,000 μm or less 2 The following is more preferable: a thickness of 20 μm or less, and a planar area of ​​2,500 μm 2 The following are even more preferred: The interval between the micro LEDs mounted on the substrate is, for example, 10 to 5,000 μm. When a set of red, green, and blue micro LEDs is mounted on the substrate as one pixel, the interval between the pixels is, for example, 10 to 2,000 μm, preferably 20 to 1,800 μm, and more preferably 500 to 1,500 μm. The interval between the micro LEDs in one pixel is, for example, 10 to 200 μm, preferably 10 to 100 μm, and more preferably 20 to 60 μm.

[0017] Process (b): Filling process As shown in FIG. 2(b), for example, the resin composition layer is fluidized by pressing and filled around the micro LEDs and between the micro LEDs. The resin composition layer filled around the micro LEDs and between the micro LEDs becomes a sealing layer. The pressing method is not particularly limited, but heat pressing and vacuum pressing are preferred. From the viewpoint of the filling property of the resin composition layer, the temperature during pressing is preferably 20 to 200° C., more preferably 30 to 150° C., further preferably 50 to 140° C., and most preferably 70 to 130° C. In order to improve the adhesion to the micro LED or the adherend, heat aging may be further performed after pressing. The heating temperature is preferably 40 to 250°C, more preferably 80 to 220°C, and even more preferably 100 to 190°C. The heating time is preferably 30 to 300 minutes, more preferably 60 to 240 minutes, and even more preferably 90 to 180 minutes. By setting the heating temperature and heating time as described above, the residual stress of the resin composition layer can be removed and the adhesion can be improved. Heat aging may be performed after the step (c) described later. The second film may be peeled off before or after heat aging.

[0018] Step (c): Etching step In step (c), etching may be performed as necessary to remove or thin the sealing layer on the optical semiconductor element. When step (c) is performed, it is preferable to perform it after peeling off the second film. By removing the excess sealing layer, the brightness of the micro LED is improved and visibility during light emission is ensured. The thickness of the sealing layer after etching is preferably about the same as the thickness of the micro LED as shown in FIG. 2(c-1) or less than the thickness of the micro LED as shown in FIG. 2(c-2). It is not necessary to completely remove the sealing layer from the micro LED, as long as it is substantially removed, and it is acceptable for some thin film to remain. It is also acceptable to omit step (c) if the brightness can be sufficiently ensured. The etching method is not particularly limited, and preferred examples include wet etching methods such as chemical polishing using chemicals, physical polishing using an abrasive, laser etching, plasma etching using argon plasma or oxygen plasma, and dry etching methods such as ion beam etching. From the viewpoint of reducing the surface unevenness, it is preferable to use plasma etching or a combination of wet etching and dry etching. The plasma etching conditions may be, for example, dry etching in an anisotropic plasma device using a mixed gas of CF4 / O2 / N2 at an output of 1500-3000 W for 180-600 seconds, where the CF4 gas supply rate is, for example, 50-100 sccm, the O2 gas supply rate is, for example, 500-1000 sccm, and the N2 gas supply rate is, for example, 50-100 sccm.

[0019] As described above, through steps (a) to (c), an encapsulating layer can be formed from the resin composition layer in the encapsulating sheet of the present disclosure. As described above, the encapsulating sheet of the present disclosure has a resin composition layer for forming an encapsulating layer sandwiched between a first film and a second film, and can be obtained by applying a coating liquid of a resin composition for forming a resin composition layer onto the second film, drying the coating liquid, and then covering the surface of the resin composition layer with the first film, or by applying a coating liquid of a resin composition for forming a resin composition layer onto the first film, drying the coating liquid, and then covering the surface of the resin composition layer with the second film.

[0020] [Resin composition layer] The resin composition layer contains a resin (A), and at least one of a polymerization initiator (B), a colorant (C), and a crosslinking agent (E), and may further contain other components. In the present disclosure, the resin (A) is a substance that has a function of bonding and fixing things together as a binder, specifically, a function of bonding and fixing a substrate having a micro LED or a micro LED.

[0021] In the present invention, it is important that the surface roughness Ra of the resin composition layer on the surface in contact with the light-emitting element 5 in step (a) shown in FIG. 2, in other words, the surface in contact with the first film in FIG. 1, is 0.02 μm or more, and it is preferably 60% or less of the thickness Ta of the resin composition layer. By using a resin composition layer having a surface roughness Ra of 0.02 μm or more, the resin composition layer is unlikely to be excessively attached to the surface of the micro LED during the process shown in FIG. 2(a), making it easy to correct the placement position. In addition, by using a resin composition layer having a surface roughness Ra of 0.02 μm or more, air is unlikely to remain at the interface between the substrate and the resin composition layer during the process shown in FIG. 2(b), resulting in a good appearance. That is, a resin composition layer having a surface roughness Ra of 0.02 μm or more is important in terms of blocking suppression and prevention, and air entrapment suppression and prevention, and the surface roughness Ra is preferably 0.03 μm or more, more preferably 0.1 μm or more, and even more preferably 0.3 μm or more. From the viewpoint of blocking suppression and prevention and air entrapment suppression and prevention, it is preferable that the surface roughness Ra is large, but if the surface roughness Ra is too large, there is a risk that the gaps between the micro LEDs and the periphery of the micro LEDs cannot be filled sufficiently without gaps during the process shown in Fig. 2(b). Therefore, the surface roughness Ra of the resin composition layer is preferably 60% or less of the thickness Ta of the resin composition layer.

[0022] The resin composition layer of the present disclosure has a glass transition temperature (Tg) of 20° C. or higher and a loss tangent (tanδ) at 100° C., as measured by dynamic viscoelasticity measurement in a torsion mode at a frequency of 1 Hz. 100 ) is important to be 0.2 or greater. By having a Tg of 20° C. or more, blocking suppression and prevention in the step (a) shown in FIG. 2 are improved. 100 When tan δ is 0.2 or more, the resin composition layer becomes more easily deformable and flowable in the step (b) shown in FIG. 2, and the suppression and prevention of air entrapment is improved. 100 is preferably from 0.3 to 2.5, more preferably from 0.3 to 2.0, and further preferably from 0.3 to 1.8. tan δ 100 When tan δ is 0.2 or more, the pressure applied to the resin composition layer in the pressing step is diffused well, and not only the air entrapment suppression and prevention properties but also the embeddability, smoothness, and adhesion to the adherend, which will be described later, are improved. 100 By making the ratio of the thickness of the sealing layer to the thickness of the micro LED equal to or less than 2.5, excessive deformation and flow of the resin composition layer during the pressing process can be suppressed, and a sufficient thickness of the sealing layer can be ensured even in the peripheral portion of the micro LED. The above-mentioned Tg and tan δ 100 is determined by dynamic viscoelasticity measurement in a torsion mode at a frequency of 1 Hz and from -50 to 150°C. tan δ is the ratio of loss modulus to storage modulus, and Tg is the temperature at the peak top of tan δ. 100 is the ratio of loss modulus to storage modulus at 100°C.

[0023] In addition, the resin composition layer of the present disclosure has a loss modulus (G'') at 100°C obtained by dynamic viscoelasticity measurement in a torsion mode at a frequency of 1 Hz. 100 ) but 5×10 3 Pa~2×10 7 Preferably, the concentration is 1×10 4 Pa~9×10 6 Pa is more preferable, and 2×10 4 Pa~5×10 5 Pa is even more preferred. G'' 100 However, it is considered that when the thickness is within the above range, the deformation and flow of the resin composition layer during the pressing step are improved, and the embedding property, smoothness, and adhesion to the adherend are improved. 100 is 2×10 7 By ensuring that the compressive strength is G'' or less, the resin composition layer can be easily deformed and flowed without dissipating energy in the pressing step, and the embedding ability into recesses is improved. 100 5×10 3 By setting the pressure to be equal to or higher than Pa, energy is dissipated in the pressing process, excessive deformation and flow of the resin composition layer can be suppressed, and a sufficient thickness of the encapsulating layer can be secured even in the peripheral portion of the micro LED. Tg and tan δ 100 Or G'' 100 can be adjusted by the type and composition of the resin (A), the type and content of the polymerization initiator (B), the type, dispersion state and content of the colorant (C), and the types and contents of the other components such as the crosslinker and monomer.

[0024] In addition, the dynamic viscoelasticity is preferably measured for a resin composition layer laminated to a thickness of 500 μm or more as described in the examples described later, and two sets of sealing sheets without a first film are prepared, the resin composition layers are bonded together with a laminator to produce a laminate of a second film / resin composition layer / second film, and the second film on one side of the laminate is peeled off, and the resin composition layers of the sealing sheets are repeatedly bonded together to laminate to a thickness of 500 μm or more, after which the dynamic viscoelasticity is measured. Alternatively, two sets of sealing sheets without a second film can be prepared, and a resin composition layer having a thickness of 500 μm or more can be formed in the same manner.

[0025] From the viewpoint of embedding property, the thickness Ta of the resin composition layer is preferably 1 to 100 μm, more preferably 2 to 60 μm, further preferably 5 to 50 μm, and particularly preferably 10 to 40 μm. From the viewpoint of light blocking property, the thicker the layer, the better. By setting the thickness Ta of the resin composition layer in the above range, the pressure applied to the resin composition layer in the pressing step is appropriately dispersed and sufficiently uniformed, thereby improving embeddability. The resin composition layer may be in the form of a single layer or a laminate of two or more layers, and in the case of two or more layers, the total thickness is referred to. The thickness Ta of the resin composition layer can be adjusted by the method for forming the resin composition layer, which will be described later. The thickness Ta in this disclosure is measured by the method described in the Examples section below.

[0026] The thickness Ta of the resin composition layer satisfies the formula (1) expressing the ratio to the thickness T2 of the second film described later, 0.1≦Ta / T2≦2, more preferably 0.2≦Ta / T2≦1.5, and further preferably 0.2≦Ta / T2≦1.2. By setting the thickness within the above range, the pressure transmission applied to the resin composition layer in the pressing step described below is controlled, and the resin composition layer flows uniformly, resulting in good embeddability.

[0027] Although there are no clear stages, the filling is considered to proceed through the following two successive stages: a stage in which the resin composition layer deforms vertically (Z-axis) toward the bottom of the recess, and a stage in which the resin composition layer, having reached the bottom of the recess, deforms horizontally (X-axis, Y-axis) so as to cover the entire bottom of the recess. In the present invention, the ease of deformation in the vertical (Z-axis) direction is called embeddability, and the tan δ of the resin composition layer is called embeddability. 100 If the fluidity of the encapsulating resin composition layer is insufficient, the encapsulating resin composition layer cannot be sufficiently filled in the corners of the recesses between multiple micro-sized LED elements, and voids are likely to occur in the corners.

[0028] In addition, the ease of deformation in the lateral (X-axis, Y-axis) directions is called smoothness, and is considered to be greatly influenced by the surface roughness Ra of the resin composition layer before pressing. If the surface roughness Ra before pressing is too large, when the encapsulating resin composition layer reaches the bottom of the recess and deforms in the lateral (X-axis, Y-axis) directions, a very small gap (about 0.5 μm) is likely to be generated between the bottom and the pressed encapsulating resin composition layer. If voids occur at the bottom or corners of the recess, light refracts and reflects at the voids, resulting in light mixing and adversely affecting the visibility of the display. When the encapsulating resin composition layer is transparent, the presence of minute voids causes light scattering, and is also observed as the size of haze. When the encapsulating resin composition layer is black, very minute voids can also cause light leakage. The presence of voids can be observed from the substrate side using a laser microscope. In the present invention, the surface roughness Ra of the interface after pressing can be determined from the state of extremely fine voids observed from the substrate side using a laser microscope, and can be evaluated as smoothness. In addition, since smoothness is related to the deformation of the resin composition layer in the lateral (X-axis, Y-axis) directions, it can be simply evaluated using a flat adherend having no recesses. Furthermore, if such voids exist, the adhesion of the formed sealing layer to the substrate decreases.

[0029] The cut level difference Rδc of the contour curve of the resin composition layer on the surface to be in contact with the object to be sealed is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.5 μm or more, and is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 6 μm or less. The cut level difference Rδc of the profile curve is the difference in level in the height direction that coincides with any two load length ratios, and in the present invention, the two load length ratios are defined as 25% and 75%.

[0030] When the slope of the unevenness on the surface of the first film is gentle, as shown diagrammatically in Figure 4(a), the cut level difference Rδc of the contour curve of the first film becomes small. When the shape of such a first film having a small cut level difference Rδc of the contour curve is inverted and transferred onto the surface of the resin composition layer, the slope of the unevenness on the surface of the resin composition layer also becomes gentle, as shown in Figure 4(a'), and the cut level difference Rδc of the contour curve of the resin composition layer also becomes small. On the other hand, when the slope of the unevenness on the surface of the first film is steep, as shown diagrammatically in Figure 4(b), the cut level difference Rδc of the contour curve of the first film becomes large, and when the shape of such a first film having a large cut level difference Rδc of the contour curve is inverted and transferred onto the surface of the resin composition layer, the unevenness and slope of the surface of the resin composition layer become steep, as shown in Figure 4(b'), and the cut level difference Rδc of the contour curve of the resin composition layer also becomes large. In the case where the surface of the resin composition layer is as shown in Fig. 4(b'), the resin composition layer is not easily attached to the surface of the micro LED in the process shown in Fig. 2(a), so not only is it easy to correct the placement position, but also it is difficult to leave a large void (air pocket) on the bottom of the recess in the process shown in Fig. 2(b). However, on the other hand, in the process shown in Fig. 2(b), it becomes necessary to fill the recess with more resin composition layer, which may result in insufficient filling of the recess or loss of smoothness. On the other hand, when the surface of the resin composition layer is as shown in Figure 4(a'), the resin composition layer has excellent filling properties into the recess in the process shown in Figure 2(b). However, in the process shown in Figure 2(a), the resin composition layer tends to stick to the surface of the micro LED, making it difficult to correct the placement position, and there is a risk that a large void (air pocket) will easily remain at the bottom of the recess in the process shown in Figure 2(b). Therefore, it is preferable that the cut level difference Rδc of the contour curve of the resin composition layer is within the above-mentioned range.

[0031] The resin composition for forming the resin composition layer can be obtained by mixing the resin (A), at least one of the polymerization initiator (B), the colorant (C), and the crosslinking agent (E), and a solvent (a dispersion medium for the colorant (C), or simply referred to as a solvent). The optional solvent is used for the purpose of adjusting the coating suitability such as viscosity when mixing the components constituting the resin composition layer. For example, ester-based, ether ester-based, ether-based, alcohol-based, aromatic-based, or other solvents compatible with the resin (A) can be appropriately used. Specifically, preferred examples include acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, cyclohexanone, toluene, xylene, isopropyl alcohol, and N-methyl-2-pyrrolidone. For stirring, a known stirring device can be used, and a disperser, mixer, shaker, homogenizer, etc. are preferred. The resin composition not containing the colorant (C) may be produced in two or more steps, firstly by mixing the resin (A) and an optional solvent to prepare a mixture, and secondly by adding the resin (A), the polymerization initiator (B) and other components as necessary. The resin composition containing the colorant (C) may be produced in two or more steps, firstly by dispersing the colorant (C) in an arbitrary solvent to obtain a dispersion, and secondly by adding the resin (A), the polymerization initiator (B) and other components as necessary. When obtaining the dispersion, the resin (A) and the dispersant may also be used.

[0032] Resin (A) The weight average molecular weight (Mw) of the resin (A) is preferably 1 million or less, more preferably 300,000 or less, and even more preferably 150,000 or less. By making the weight average molecular weight (Mw) of the resin (A) 1 million or less, entanglement of molecular chains becomes easier to be loosened in the heat aging process, and adhesion is improved. The lower limit of the weight average molecular weight (Mw) of the resin (A) is not particularly limited, but is preferably at least 400, more preferably at least 900, even more preferably at least 3000, even more preferably at least 5000, and most preferably at least 10,000. By making the weight average molecular weight (Mw) of the resin (A) at least 400, the coating strength of the resin composition layer is improved. The weight average molecular weight (Mw) is a value measured in terms of polystyrene by gel permeation chromatography (GPC). The weight average molecular weight (Mw) in the present disclosure is measured by the method described in the Examples below.

[0033] The resin (A) may be used alone or in combination of two or more. The content of the resin (A) is preferably 10 to 98 mass%, more preferably 25 to 95 mass%, and even more preferably 60 to 90 mass%, based on the total amount (100 mass%) of the resin composition layer. When two or more types of resin (A) are contained, the content of each of the resins (A) is preferably 5 mass% or more, and the total content is preferably within the above range. By setting the content of the resin (A) within the above range, in the case where the colorant (C) is contained, compatibility with the colorant (C) is improved, and the light-shielding properties are improved.

[0034] Suitable examples of the resin (A) include (meth)acrylic resin (a1), urethane resin (a2) such as polyurethane resin or polyurethane urea resin, epoxy resin (a3), maleic acid resin, styrene-maleic acid copolymer, polystyrene resin, polybutadiene resin, polyester resin, condensation type polyester resin, addition type polyester resin, melamine resin, polycarbonate resin, oxetane resin, phenoxy resin, polyimide resin, polyamideimide resin, alkyd resin, amino resin, polyamide resin, polylactic acid resin, oxazoline resin, benzoxazine resin, silicone resin, fluorine resin, butyral resin, chlorinated polyethylene, chlorinated polypropylene, polyvinyl chloride, vinyl chloride-vinyl acetate copolymer, polyvinyl acetate, vinyl resin, rubber resin, cyclized rubber resin, cellulose, polyethylene (HDPE, LDPE), etc. From the viewpoint of embeddability, it is preferable to include at least one of (meth)acrylic resin (a1), urethane resin (a2), and epoxy resin (a3). Furthermore, from the viewpoint of adhesion, it is more preferable that the layer contains a (meth)acrylic resin (a1).

[0035] The resin (A) preferably has one or more functional groups that can be used in a polymerization / crosslinking reaction by heat or light. The functional groups may be appropriately selected depending on the reactivity between the resins (A) and with the polymerization initiator (B) and crosslinking agent (E) described below, and may be self-crosslinkable functional groups. Examples of the functional group include a hydroxyl group, a carboxyl group, an amino group, an epoxy group, an oxetanyl group, an oxazoline group, an oxazine group, an aziridine group, a thiol group, an isocyanate group, a blocked isocyanate group, a silanol group, a (meth)acryloyl group, an N-vinyl group, a vinyl ether group, an allyl group, an unsaturated carboxylic acid group, etc. Radical polymerizable functional groups such as a (meth)acryloyl group, an N-vinyl group, a vinyl ether group, an allyl group, and an unsaturated carboxylic acid group are preferred.

[0036] [(Meth)acrylic resin (a1)] In the present disclosure, the (meth)acrylic resin (a1) is an acrylic copolymer obtained by copolymerizing a (meth)acrylic acid ester monomer, and is a polymer having 2 to 20,000 monomer-based structural units. A suitable example of the (meth)acrylic acid ester monomer is a (meth)acrylic acid alkyl ester monomer. When a functional group that can be used in a polymerization / crosslinking reaction is introduced, a (meth)acrylic copolymer obtained by copolymerizing a functional group-containing monomer and a (meth)acrylic acid ester monomer is preferred. The (meth)acrylic resin (a1) of the present disclosure does not include compounds containing two or more urethane bonds in one molecule and compounds having two or more epoxy groups in one molecule.

[0037] The (meth)acrylic acid alkyl ester monomer is a compound in which an alkyl group or a cycloalkyl group is introduced by esterifying (meth)acrylic acid, and the alkyl group or the cycloalkyl group may be any of a linear, branched, or cyclic saturated aliphatic hydrocarbon group. The saturated aliphatic hydrocarbon group is preferably a saturated aliphatic hydrocarbon group having 1 to 20 carbon atoms, and more preferably a saturated aliphatic hydrocarbon group having 1 to 12 carbon atoms. Specific examples include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, and (meth)acrylic acid. Decyl, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, 4-n-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, etc. Among these, in view of the dispersibility of the colorant (C), it is particularly preferable to use methyl (meth)acrylate, n-butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate, and it is most preferable to use methyl (meth)acrylate and n-butyl (meth)acrylate.

[0038] From the viewpoint of adhesion, the (meth)acrylic resin (a1) preferably contains 1 to 100 mass %, more preferably 20 to 99.5 mass %, and even more preferably 80 to 99 mass %, of structural units derived from (meth)acrylic acid alkyl ester monomers, based on 100 mass % of the monomers constituting the (meth)acrylic resin (a1).

[0039] The (meth)acrylic resin (a1) preferably has a structural unit derived from a functional group-containing monomer and / or an unsaturated bond. Examples of functional group-containing monomers include carboxyl group-containing monomers, hydroxyl group-containing monomers, epoxy group-containing monomers, and amino group-containing monomers. By including a functional group-containing monomer, the cohesive force of the resin (A) is improved, and a tough resin composition layer is obtained. In particular, it is preferable to include a carboxyl group-containing monomer, a hydroxyl group-containing monomer, and an epoxy group-containing monomer.

[0040] Examples of the carboxyl group-containing monomer include (meth)acrylic acid, β-carboxyethyl (meth)acrylate, p-carboxybenzyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, citraconic acid, and isocrotonic acid. Among these, (meth)acrylic acid is preferred from the viewpoint of adhesion.

[0041] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate. Among these, from the viewpoint of adhesion, 4-hydroxybutyl (meth)acrylate and 2-hydroxyethyl (meth)acrylate are more preferred.

[0042] Examples of the amino group-containing monomer include monoalkylamino (meth)acrylates such as monomethylaminoethyl (meth)acrylate, monoethylaminoethyl (meth)acrylate, monomethylaminopropyl (meth)acrylate, and monoethylaminopropyl (meth)acrylate.

[0043] The (meth)acrylic resin (a1) preferably contains structural units derived from functional group-containing monomers in a total amount of 0.1 to 20 mass% based on 100 mass% of the monomers constituting the (meth)acrylic resin (a1). By setting the content within the above range, the adhesive strength can be adjusted. It is preferable that the content of structural units derived from a carboxyl group-containing monomer is 0.1 to 10% by mass. When the content is within this range, adhesion can be improved. It is preferable that the content of structural units derived from hydroxyl group-containing monomers is 0.1 to 10% by mass. When the content is within this range, adhesion can be improved.

[0044] For the purpose of introducing an unsaturated bond into the (meth)acrylic resin (a1), a monomer having an epoxy group or a monomer having an isocyanate group can be used. The (meth)acrylic resin (a1) having an unsaturated bond can be obtained by the following two-stage reaction. First, a monomer having a carboxyl group such as (meth)acrylic acid is used to obtain a (meth)acrylic copolymer having a carboxyl group, or a monomer having a hydroxyl group such as 2-hydroxyethyl (meth)acrylate is used to obtain a (meth)acrylic copolymer having a hydroxyl group. Then, it is preferable to react at least a part (10 to 100 mol%) of the carboxyl group or hydroxyl group of the (meth)acrylic copolymer with an epoxy group or an isocyanate group in a monomer having an unsaturated bond such as an epoxy group or an isocyanate group and a (meth)acryloyl group to introduce an unsaturated bond such as a (meth)acryloyl group into the (meth)acrylic resin (a1). In addition, a monomer having an unsaturated bond such as an epoxy group or an isocyanate group and a (meth)acryloyl group may be called a modifier in the sense of modifying the (meth)acrylic copolymer. There is no limitation on the amount of unsaturated bonds such as (meth)acryloyl groups introduced. The (meth)acrylic resin (a1) may have a carboxy group or a hydroxyl group in addition to unsaturated bonds such as (meth)acryloyl groups.

[0045] Examples of monomers having an epoxy group and an unsaturated bond such as a (meth)acryloyl group include glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, and 6-methyl-3,4-epoxycyclohexylmethyl (meth)acrylate. Among these, it is preferable to use glycidyl (meth)acrylate from the viewpoint of reactivity. It is preferable that the number of epoxy groups in the monomer having an epoxy group and an unsaturated bond such as a (meth)acryloyl group is one or less per molecule. Examples of the monomer having an isocyanate group and an unsaturated bond such as a (meth)acryloyl group include Karenz MOI and AOI (Resonac Corporation).

[0046] The (meth)acrylic resin (a1) may contain structural units derived from other monomers copolymerizable with (meth)acrylic acid alkyl esters and functional group-containing monomers. Examples of such monomers include monomers having an alkyleneoxy group and other vinyl monomers. Examples of such monomers include methoxyethyl acrylate, methoxydiethylene glycol acrylate, vinyl acetate, vinyl crotonate, styrene, acrylonitrile, and acrylamide. The structural units derived from the other monomers are preferably 0.1 to 20% by mass in 100% by mass of the monomers constituting the (meth)acrylic resin (a1).

[0047] The (meth)acrylic resin (a1) is obtained by polymerizing the above-mentioned (meth)acrylic monomer mixture. During polymerization, a polymerization initiator can be used as necessary. The amount of the polymerization initiator is, for example, 0.01 to 10 parts by mass relative to 100 parts by mass of the monomer mixture. The polymerization method is not limited. For example, the polymerization can be performed by solution polymerization, bulk polymerization, emulsion polymerization, or suspension polymerization, and solution polymerization is most preferable because of ease of polymerization control. Examples of the solvent used in solution polymerization include acetone, methyl ethyl ketone, methyl isobutyl ketone, methyl acetate, ethyl acetate, butyl acetate, toluene, xylene, anisole, cyclohexanone, and isopropyl alcohol. The polymerization temperature can be, for example, 60 to 120°C, and the polymerization time can be about 2 to 12 hours.

[0048] The polymerization initiator is preferably a radical polymerization initiator. As the radical polymerization initiator, peroxides and azo compounds are suitable. Any of the thermal radical polymerization initiators described below can be used, and specifically, 2,2'-azobisisobutyronitrile (abbreviation: AIBN) is preferred.

[0049] [Urethane resin (a2)] In the present disclosure, the urethane resin (a2) is a compound containing two or more urethane bonds in one molecule. The urethane resin can be obtained by reacting a polyisocyanate with a polyol. The polyisocyanate may have two or more isocyanate groups in one molecule, and from the viewpoint of dispersibility of the colorant (C), diisocyanate or triisocyanate is preferable, and diisocyanate is more preferable. The diisocyanate may be appropriately selected from known aliphatic diisocyanates such as hexamethylene diisocyanate and known aromatic diisocyanates such as benzene-1,3-diisocyanate. In addition, an isocyanate-terminated prepolymer obtained by reacting a polyol with an excess of polyisocyanate may be used as an intermediate of the urethane resin. The polyol may have two or more hydroxyl groups in one molecule, and from the viewpoint of dispersibility of the colorant (C), a diol or triol is preferable, and a diol is more preferable. The diol may be appropriately selected from known aliphatic diols such as ethylene glycol and known aromatic diols such as benzene diol. In addition, prepolymers such as polyether polyols, polyester polyols, and polycarbonate polyols may be used.

[0050] The urethane resin (a2) may be a polyurethane urea resin further having a urea bond. The polyurethane urea resin can be synthesized, for example, by reacting a urethane resin having an isocyanate group at its terminal with a polyamine. The polyamine may be any one having two or more amino groups in one molecule, and from the viewpoint of dispersibility of the colorant (C), a diamine or triamine is preferable, and a diamine is more preferable. The diamine can be appropriately selected from known aliphatic diamines such as ethylenediamine and known aromatic diamines such as phenylenediamine.

[0051] From the viewpoint of dispersibility of the colorant (C), the urethane resin (a2) preferably further has a radical polymerizable functional group such as a (meth)acryloyl group, an N-vinyl group, a vinyl ether group, an allyl group, an unsaturated carboxylic acid group, etc., as a functional group, and more preferably has a (meth)acryloyl group. Specifically, the (meth)acryloyl group can be introduced by addition reaction of the above-mentioned polyol, diisocyanate or triisocyanate with an acrylate having a hydroxyl group.

[0052] [Epoxy resin (a3)] In the present disclosure, the epoxy resin (a3) ​​is a compound having two or more epoxy groups in one molecule. The epoxy resin (a3) ​​also includes a compound further added to a functional group. As the functional group, it is preferable that the epoxy resin has a radical polymerizable functional group such as a (meth)acryloyl group, an N-vinyl group, a vinyl ether group, an allyl group, an unsaturated carboxylic acid group, etc., and it is more preferable that the epoxy resin has a (meth)acryloyl group. Regarding the properties of the epoxy resin (a3), the use of a liquid form can improve adhesion, while the use of a solid form can improve film-forming properties of the resin composition layer. As the epoxy resin (a3), for example, glycidyl ether type epoxy resin, glycidyl amine type epoxy resin, glycidyl ester type epoxy resin, cyclic aliphatic (alicyclic) epoxy resin, bisphenol type epoxy resin, hydrogenated bisphenol type epoxy resin, etc. are preferable. Moreover, from the viewpoint of adhesion, it is more preferable that the epoxy resin (a3) ​​is a bisphenol type epoxy resin or a high purity hydrogenated epoxy resin. As a compound in which a radically polymerizable functional group is added as a functional group to one or more epoxy groups, bisphenol A type diglycidyl ether diacrylate is preferred.

[0053] Examples of the glycidyl ether type epoxy resin include cresol novolac type epoxy resin, tris(glycidyloxyphenyl)methane, and tetrakis(glycidyloxyphenyl)ethane. Examples of the glycidylamine type epoxy resin include tetraglycidyldiaminodiphenylmethane and tetraglycidylmetaxylylenediamine. Examples of the glycidyl ester type epoxy resin include diglycidyl phthalate, diglycidyl hexahydrophthalate, and diglycidyl tetrahydrophthalate. Examples of cyclic aliphatic (alicyclic) epoxy resins include epoxycyclohexylmethyl-epoxycyclohexanecarboxylate, bis(epoxycyclohexyl)adipate, and the like. Examples of bisphenol type epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy crosslinkers, bisphenol S type epoxy resins, bisphenol AD ​​type epoxy resins, etc. Bisphenol A type epoxy resins are particularly preferred from the viewpoint of adhesion. Examples of hydrogenated bisphenol type epoxy resins include hydrogenated bisphenol A type epoxy resins, hydrogenated bisphenol F type epoxy resins, etc. In particular, hydrogenated bisphenol A type epoxy resins are preferred from the viewpoint of adhesion.

[0054] [Polymerization initiator (B)] In the present embodiment, either a thermal polymerization initiator or a photopolymerization initiator can be used, and it is preferable to use a thermal polymerization initiator from the viewpoint of the film-forming property and adhesion of the resin composition layer. When either a thermal polymerization initiator or a photopolymerization initiator is used, it is preferable that the resin (A) has one or more radical polymerizable functional groups in one molecule as functional groups. Examples of the radical polymerizable functional group include a (meth)acryloyl group, an N-vinyl group, a vinyl ether group, and an allyl group, and a (meth)acryloyl group is preferable.

[0055] In the present embodiment, the thermal polymerization initiator may be a thermal radical polymerization initiator or a thermal cationic polymerization initiator. From the viewpoint of storage stability of the resin composition layer, the thermal radical polymerization initiator is preferred. The thermal radical polymerization initiator has a function of generating radicals by heat, and examples of the thermal radical polymerization initiator include organic peroxide polymerization initiators and azo thermal polymerization initiators.

[0056] Examples of the organic peroxide polymerization initiator include dialkyl peroxides such as diacetyl peroxide, di-t-butyl peroxide, di-t-hexyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, 1,3-bis(t-butylperoxyisopropyl)hexane, and (2-ethylhexanoyl)(t-butyl)peroxide; Dipropionyl peroxide, t-butyl peroxyacetate, t-butyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, bis(3,5,5-trimethylhexanoyl)peroxide, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, α-cumyl peroxyneodecanoate, t-butyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, t-butyl peroxyneoheptanoate, t-hexyl peroxypivalate, t-butyl peroxypivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, t-amyl peroxy-2-ethylhexanoate, t-butyl peroxy-2-ethylhexanoate, Peroxyesters such as t-butylperoxyisobutyrate, di-t-butylperoxyhexahydroterephthalate, 1,1,3,3-tetramethylbutylperoxy-3,5,5-trimethylhexanate, t-amylperoxy-3,5,5-trimethylhexanoate, t-butylperoxy-3,5,5-trimethylhexanoate, dibutylperoxytrimethyladipate, 2,5-dimethyl-2,5-di-2-ethylhexanoylperoxyhexane, t-hexylperoxy-2-ethylhexanoate, t-hexylperoxyisopropyl monocarbonate, t-butylperoxylaurate, t-butylperoxyisopropyl monocarbonate, and t-butylperoxy-2-ethylhexyl monocarbonate; Ketone peroxides such as methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, acetylacetone peroxide, cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, methylcyclohexanone peroxide, t-butyl benzoate, and pivaloyl t-butyl peroxide; Peroxyketals such as 2,2-bis(t-butylperoxy)butane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, and 4,4-bis(t-butylperoxy)butylpentanoate; Hydroperoxides such as t-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, 2,5-dimethylcyclohexane-2,5-dihydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, and p-menthane hydroperoxide; Diacyl peroxides such as dibenzoyl peroxide, didecanoyl peroxide, dilauroyl peroxide, diisobutyryl peroxide, bis-3,5,5-trimethylhexanol peroxide, m-toluoylbenzoyl peroxide, succinic acid peroxide, and 2,4-dichlorobenzoyl peroxide; Examples of peroxydicarbonates include, but are not limited to, bis(t-butylcyclohexyl)peroxydicarbonate, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butylperoxyisopropyl carbonate, di-2-ethylhexyl peroxydicarbonate, di-sec-butyl peroxycarbonate, di-3-methoxybutyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, t-amylperoxyisopropyl carbonate, t-butylperoxy-2-ethylhexyl carbonate, and 6-bis(t-butylperoxycarboxyloxy)hexane. From the viewpoint of storage stability, dialkyl peroxides are preferred, and di-t-butyl peroxide is more preferred.

[0057] Examples of the azo thermal polymerization initiator include 2,2'-azobisbutyronitriles such as 2,2'-azobisisobutyronitrile and 2,2'-azobis(2-methylbutyronitrile); 2,2'-azobisvaleronitrile such as 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile); 1,1'-azobis-1-alkanenitriles such as 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2-hydroxymethylpropionitrile), 2,2'-azobispropionitriles such as 2,2'-azobis(2-hydroxymethylpropionitrile); 2,2'-azobispropionamides such as 2,2'-azobis(N-butyl-2-methylpropionamide) and 2,2'-azobis(N-cyclohexyl-2-methylpropionamide); Other examples include dimethyl 2,2'-azobis(2-methylpropionate), 2,2'-azobis[2-(2-imidazolin-2-yl)propane], and 1-[(1-cyano-1-methylethyl)azo]formamide. Examples of azo compounds having a carboxyl group or a hydroxyl group include, but are not limited to, 4,4'-azibis(4-cyanopentanoic acid), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide), and 2,2'-azobis(N-(carboxyethyl)-2-methylpropionamidine) tetrahydrate. From the viewpoint of storage stability, 2,2'-azobispropionamides are preferred, and 2,2'-azobis(N-butyl-2-methylpropionamide) is more preferred.

[0058] The 10-hour half-life temperature of the thermal radical polymerization initiator is preferably 60 to 200° C., more preferably 80 to 180° C., further preferably 100 to 150° C., and most preferably 105 to 130° C. By setting the temperature to 60° C. or higher, the storage stability of the resin composition layer can be improved, and by setting the temperature to 200° C. or lower, the heat aging step of the sealing layer can be shortened.

[0059] The 10-hour half-life temperature is the temperature at which the thermal polymerization initiator is thermally decomposed and reduced to half of its initial value after 10 hours. Specifically, a thermal polymerization initiator solution is prepared using a solvent that is inert to the radicals of the thermal polymerization initiator, and is sealed in a glass tube that has been substituted with nitrogen. This is immersed in a thermostatic chamber set at a specified temperature for 10 hours to cause thermal decomposition, and the amount of remaining thermal polymerization initiator is measured. This series of steps is carried out at several temperatures, and the half-life can be calculated from the straight line obtained by plotting.

[0060] The content of the thermal radical polymerization initiator is preferably 0.01 to 20% by mass, more preferably 0.05 to 10% by mass, and even more preferably 0.1 to 8% by mass, based on the total amount (100% by mass) of the resin composition layer. By setting the content within the above range, the adhesion can be suitably adjusted.

[0061] Among the thermal polymerization initiators, the thermal cationic polymerization initiator has the function of generating ions by heat. The thermal cationic polymerization initiator includes, as cationic components, sulfonium cations, quaternary ammonium cations, and iodonium cations. The anionic components include, for example, hexafluoroantimony anion, hexafluorophosphorus anion, tetrakis(pentafluorophenyl)borate anion, and trifluoromethanesulfonic acid.

[0062] Examples of the photopolymerization initiator include triazine-based photopolymerization initiators, borate-based photopolymerization initiators, carbazole-based photopolymerization initiators, acetophenone-based photopolymerization initiators, and oxime ester-based photopolymerization initiators. The acetophenone-based photopolymerization initiators and oxime ester-based photopolymerization initiators are preferred because they are less likely to yellow during the heat aging process. From the viewpoint of preventing yellowing, the content of the photopolymerization initiator is preferably 0.5 to 10 mass %, and more preferably 0.5 to 5 mass %, based on the total amount (100 mass %) of the resin composition layer.

[0063] [Colorant (C)], [Dispersion (D)] The colorant (C) may be any of inorganic pigments, organic pigments, and dyes, and may be mixed to obtain a desired color. The color is not particularly limited, but black is preferred from the viewpoint of light blocking, and white is preferred from the viewpoint of reflection. To achieve a black color, multiple pigments can be subtractively mixed to form a mixed colorant. Black pigments are more preferable from the viewpoint of dispersibility. By using a black pigment to make the resin composition layer black and sealing the spaces between and around multiple micro LEDs, the sealing layer functions as a black matrix (light-shielding layer), making the light emitted by the micro LEDs appear more vivid. Examples of black pigments include carbon black, carbon nanotubes (CNT), perylene black, titanium black, iron black, aniline black, chromium iron oxide, etc. From the viewpoint of adhesion, carbon black is preferred.

[0064] Carbon blacks used in the present disclosure include channel black, furnace black, Known carbon blacks such as carbon black, thermal black, lamp black, acetylene black, and ketjen black can be used. Specific examples of carbon black include Birla Carbon's "Raven 3500, 1180, 1080 Ultra, 1060 Ultra, 1040," Tokai Carbon's "TOKABLACK #8300, #7360SB," Orion Engineered Carbons' "Special Black 350, 250, 100, 550, 5, 4, 4A, 6," "Nipex 160IQ, 170IQ," "Printex U, V, 140U, 140V, 95, 90, 85, 80, 75, 55, 45, P, 60, L6, L, 300, 30, 3, 35, 25, A, G," and "Color Black FW 200, FW 2, S170," and Cabot's "REGAL 400R, 330R, 250R," "MOGUL Examples include "MONARCH1300, 280", "MA7, 8, 11, 14, 77, 100, 100R, 100S, 220, 230", "#2650, #2600, #2350, #2300, #1000, #980, #970, #960, #950, #900, #850, #750B, #650B, #52, #47, #45, #45L, #44, #40, #33, #32, #30, #25, #20, #10, #5, #95," and others manufactured by Mitsubishi Chemical Corporation. From the viewpoint of dispersibility, carbon black should have a specific surface area of ​​50 to 400 m by the BET method. 2 / g, a volatile content of 0.1 to 10 wt %, and a pH value of 2 to 10 are preferred, with a pH of 3 to 8 being more preferred, and a pH of 3 to 6 being even more preferred.

[0065] When the purpose is to form a black matrix (light-shielding layer), the colorant (C) preferably has an average primary particle diameter (hereinafter, particle diameter) of 10 to 100 nm. By making the particle diameter 10 nm or more, the viscosity of the resin composition can be easily maintained at a level suitable for coating. Furthermore, by making the particle diameter 100 nm or less, the degree of blackness is improved, and high light-shielding performance is exhibited. Note that, when the particle shape of the colorant (C) has an average aspect ratio (long axis length / short axis length) of 1.5 or more, the particle diameter is obtained by averaging the long axis length. The particle size of the colorant (C) can be determined from the average value of about 20 primary particles observed in an image magnified about 50,000 to 1,000,000 times by a transmission electron microscope (TEM).

[0066] When the purpose is to form a black matrix (light-shielding layer), the content of the colorant (C) is preferably 5 to 45 mass % based on the total amount (100 mass %) of the light-shielding layer, more preferably 15 to 35 mass %, and even more preferably 20 to 30 mass %. By setting the content of the colorant (C) within the above range, the light-shielding property is at an excellent level.

[0067] When the purpose is to form a reflective layer, the colorant (C) may be, for example, titanium oxide, zinc oxide, lithopone, etc. From the viewpoint of whiteness, a white pigment is preferred, and among them, titanium oxide is preferred from the viewpoint of dispersibility. By using a white pigment to make the resin composition layer white and sealing the gaps between and around a plurality of micro LEDs, the sealing layer functions as a reflective layer, and the brightness of the micro LEDs can be further increased.

[0068] As the titanium oxide used in the present disclosure, known titanium oxides such as rutile titanium oxide and anatase titanium oxide can be used. From the viewpoint of deterioration of the resin due to light, rutile titanium oxide is preferred. Specific examples of rutile titanium dioxide include "Tipake R-820, R-830, R-930, R-550, R-630, R-680, R-670, R-680, R-670, R-780, R-850, CR-50, CR-57, CR-80, CR-90, 90-2, CR-93, CR-95, CR-97, CR-63, CR-58, UT771" manufactured by Ishihara Sangyo Kaisha, "Tipure R-101, R-103, R-104, R-105, R-108, R-900, R-902+, R-960, R-706" manufactured by DuPont, and "TITONE" manufactured by Sakai Chemical Industry Co., Ltd. Examples include R-25, R-21, R-32, R-7E, R-5N, R-62N, R-42, R-45M, GTR-100, and D-918.

[0069] The average particle size of the rutile type titanium oxide is preferably 0.1 μm or more and 0.9 μm or less, and more preferably 0.2 μm or more and 0.7 μm or less. By making the particle size 0.1 μm or more, it is easy to prevent the aggregation and precipitation of titanium oxide in the coating liquid for forming the resin composition layer. Furthermore, by making the particle size 0.9 μm or less, the whiteness is improved and high reflectivity is exhibited. Note that, when the particle shape of the colorant (C) has an average aspect ratio (long axis length / short axis length) of 1.5 or more, the particle size is obtained by averaging the long axis length. Note that the particle size of the colorant (C) can be obtained from the average value of about 20 primary particles observed from an image magnified about 50,000 to 1,000,000 times by a transmission electron microscope (TEM).

[0070] It is preferable to disperse the colorant (C) in the resin (A) and use it as a dispersion (D) from the viewpoint of adjusting the film-forming property and light-shielding property of the resin composition layer. The dispersing machine used for mechanical disintegration in the dispersion process may be any dispersing machine that is generally used, and examples thereof include ball mills, roll mills, sand mills, bead mills, and nanomizers. Among them, bead mills are preferably used. Examples of such machines include super mills, sand grinders, agitator mills, grain mills, dyno mills, pearl mills, and cobol mills (all trade names).

[0071] In the present disclosure, from the viewpoint of storage stability of the dispersion, it is preferable to use a dispersant in the dispersion treatment of the colorant (C). In the present disclosure, the dispersant has a function of imparting a repulsive force between particles so that the particles divided through the above-mentioned dispersion treatment do not aggregate again. As the dispersant, a conventionally known compound can be used, for example, a cationic, anionic or nonionic surfactant, a cationic, anionic or nonionic polymer dispersant, or a pigment derivative dispersant. From the viewpoint of the storage stability of the dispersion, the pigment derivative dispersant is preferred.

[0072] Pigment derivative dispersants are compounds having an acidic group, a basic group, a neutral group, etc. in the organic dye residue. Examples include compounds having an acidic substituent such as a sulfo group, a carboxyl group, or a phosphoric acid group, as well as amine salts thereof, compounds having a basic substituent such as a sulfonamide group, an amide group, or a tertiary amino group at the end, and compounds having a neutral substituent such as a phenyl group or a phthalimidoalkyl group. Examples of organic dyes include phthalocyanine pigments, diketopyrrolopyrrole pigments, anthraquinone pigments, quinacridone pigments, dioxazine pigments, perinone pigments, perylene pigments, thiazine indigo pigments, triazine pigments, benzimidazolone pigments, indole pigments such as benzoisoindole, isoindoline pigments, isoindolinone pigments, quinophthalone pigments, naphthol pigments, threne pigments, metal complex pigments, azo pigments such as azo, disazo, and polyazo, etc. By using these pigment dispersants, it becomes possible to prevent the colorant (C) contained in the resin composition from aggregating over time and to maintain good light-shielding properties.

[0073] The content of the pigment dispersant (total content when two or more kinds are included) is preferably 0.01 to 10 mass% and more preferably 0.1 to 5 mass% based on the total amount (100 mass%) of the resin composition layer. By containing 0.01 mass% or more of the pigment dispersant, the light blocking property is improved, and by containing 10 mass% or less, the viscosity of the black resin composition for forming the sealing layer falls within a suitable range, and the coating suitability is improved.

[0074] [Crosslinker (E)] The resin composition layer of the present disclosure may contain a crosslinking agent (E). The crosslinking agent (E) crosslinks with the reactive functional groups of the resin (A) during heat pressing or heat aging in the pressing process, thereby increasing the cohesive force of the resin composition layer and improving adhesion. The crosslinking agent (E) has a plurality of functional groups capable of reacting with the functional groups of the resin (A). Examples of the crosslinking agent (E) include known compounds such as acid anhydride group-containing compounds, imidazole compounds, isocyanate compounds, aziridine compounds, amine compounds, and compounds having an epoxy group. The loss tangent (tanδ) of the resin composition layer is preferably 0.01 to 0.01.100 From the viewpoint of adjusting the amount of the copolymer, an isocyanate compound, a compound having an epoxy group, an aziridine compound, or an imidazole compound is preferred.

[0075] The isocyanate compound is an isocyanate having two or more isocyanate groups. When the resin (A) has a hydroxyl group or an amino group, it can react with the isocyanate group. The isocyanate compound is preferably, for example, an isocyanate monomer such as an aromatic polyisocyanate, an aliphatic polyisocyanate, an araliphatic polyisocyanate, or an alicyclic polyisocyanate, as well as a biuret, a nurate, or an adduct thereof. The isocyanate compound is preferably a trifunctional isocyanate compound from the viewpoint of forming a sufficient crosslinked structure. The isocyanate compound is more preferably an adduct which is a reaction product between an isocyanate monomer and a trifunctional low-molecular active hydrogen-containing compound, and a nurate. Examples of the adduct include a trimethylolpropane adduct of hexamethylene diisocyanate, a trimethylolpropane adduct of tolylene diisocyanate, and a trimethylolpropane adduct of isophorone diisocyanate. Examples of the nurate include a nurate of hexamethylene diisocyanate, a nurate of tolylene diisocyanate, and a nurate of isophorone diisocyanate. Of these, a trimethylolpropane adduct of hexamethylene diisocyanate, a trimethylolpropane adduct of tolylene diisocyanate, and a trimethylolpropane adduct of isophorone diisocyanate are more preferred.

[0076] When the resin (A) has a carboxy group, a compound having an epoxy group can be suitably used as the crosslinking agent (E). As the compound having an epoxy group, a glycidyl ether type epoxy compound, a glycidyl amine type epoxy compound, a glycidyl ester type epoxy compound, a cyclic aliphatic (alicyclic) epoxy compound, etc. are preferable.

[0077] Examples of the glycidyl ether type epoxy compounds include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol S type epoxy compounds, bisphenol AD ​​type epoxy compounds, cresol novolac type epoxy compounds, phenol novolac type epoxy compounds, α-naphthol novolac type epoxy compounds, bisphenol A type novolac type epoxy compounds, dicyclopentadiene type epoxy compounds, tetrabromobisphenol A type epoxy compounds, brominated phenol novolac type epoxy compounds, tris(glycidyloxyphenyl)methane, and tetrakis(glycidyloxyphenyl)ethane.

[0078] Examples of the glycidylamine type epoxy compound include tetraglycidyldiaminodiphenylmethane, triglycidyl paraaminophenol, triglycidyl meta-aminophenol, and tetraglycidyl meta-xylylenediamine.

[0079] Examples of the glycidyl ester type epoxy compound include diglycidyl phthalate, diglycidyl hexahydrophthalate, and diglycidyl tetrahydrophthalate.

[0080] Examples of cyclic aliphatic (alicyclic) epoxy compounds include epoxycyclohexylmethyl-epoxycyclohexanecarboxylate, bis(epoxycyclohexyl)adipate, and the like.

[0081] Examples of the aziridine compound include trimethylolpropane tris[3-(aziridin-1-yl)propionate], tetramethylolmethane-tri-β-aziridinylpropionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide), tris-2,4,6-(1-aziridinyl)-1,3,5-triazine, and 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane.

[0082] The imidazole compounds are 2-methylimidazole, 2-phenyl-4-methylimidazole, 2,4-dimethylimidazole, 2-phenylimidazole, imidazole, 2-undecylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[ Examples of the imidazole compounds include 2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole. Further examples include compounds with improved storage stability, such as imidazole compounds encapsulated in microcapsules.

[0083] The content of the crosslinking agent (E) is preferably 0.01 to 30% by mass, more preferably 0.05 to 20% by mass, and even more preferably 0.1 to 10% by mass, based on the total amount (100% by mass) of the resin composition layer. By setting the content within the above range, the adhesion can be suitably adjusted.

[0084] [Other ingredients] The resin composition layer of the present disclosure may contain other components within the scope of the present disclosure. For example, a silane coupling agent, a monomer, an inorganic filler, a surface adjustment additive, a curing accelerator, a curing retarder, a softener, an antistatic agent, a lubricant, an antiblocking agent, an adhesion improver, etc. can be added. It is preferable to contain a silane coupling agent from the viewpoint of improving adhesion to a glass substrate on which a micro LED is mounted. In addition, when the resin (A) has a polymerizable unsaturated bond, a monomer can be contained so as to contribute to the formation of a sealing layer.

[0085] A silane coupling agent is a compound in which a hydrolyzable group such as a methoxy group or an ethoxy group and a functional group such as an epoxy group are bonded to a silicon atom via an alkylene group. Examples of the silane coupling agent include: alkoxysilane compounds having a (meth)acryloxy group, such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropyltripropoxysilane, 3-(meth)acryloxypropyltributoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane; Alkoxysilane compounds having a vinyl group, such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, vinyltributoxysilane, vinylmethyldimethoxysilane, and vinylmethyldiethoxysilane; alkoxysilane compounds having an amino group, such as 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltripropoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane; alkoxysilane compounds having a mercapto group, such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltripropoxysilane, 3-mercaptopropylmethyldimethoxysilane, and 3-mercaptopropylmethyldiethoxysilane; alkoxysilane compounds having one epoxy group, such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyltripropoxysilane, 3-glycidoxypropyltributoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; Tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxy tetraalkoxysilane compounds such as silane; Examples of the silane include 3-chloropropyltrimethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, n-decyltrimethoxysilane, n-decyltriethoxysilane, styryltrimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, hexamethyldisilazane, and silicone resins having alkoxysilyl groups in the molecule. From the viewpoint of adhesion, an alkoxysilane compound is preferred, and 3-glycidoxypropyltrimethoxysilane is more preferred. In addition, when a resin (A) having a polymerizable unsaturated bond is used, an alkoxysilane compound having a (meth)acryloxy group is preferably used.

[0086] [monomer] In the present embodiment, the monomer means a compound having a radical polymerizable functional group, which is the minimum structural unit for constituting a polymer. Examples of the radical polymerizable functional group include a (meth)acryloyl group, an N-vinyl group, a vinyl ether group, and an allyl group. The monomer may be a monofunctional monomer or a polyfunctional monomer. In this specification, the term "monofunctional" refers to a compound having only one radical polymerizable functional group in one molecule, and "bifunctional" and "trifunctional" refer to compounds having two and three radical polymerizable functional groups in one molecule, respectively. In this specification, bifunctional or more functional compounds are collectively referred to as "polyfunctional". By containing a monomer, the film-forming property of the resin composition layer is adjusted, and the adhesion is improved.

[0087] Specific examples of the monomer include, but are not limited to, a monofunctional (meth)acrylate monomer having one (meth)acryloyl group in the molecule, a monofunctional vinyl monomer having one N-vinyl group in the molecule, a bifunctional (meth)acrylate monomer having two (meth)acryloyl groups in the molecule, a bifunctional (meth)acrylate monomer having one (meth)acryloyl group and one allyl group in the molecule, a trifunctional (meth)acrylate monomer having three (meth)acryloyl groups in the molecule, a tetrafunctional (meth)acrylate monomer having four acryloyl groups in the molecule, a pentafunctional (meth)acrylate monomer having five (meth)acryloyl groups in the molecule, and a hexafunctional (meth)acrylate monomer having six (meth)acryloyl groups in the molecule.

[0088] The content of the monomer can be in the range of 30% by mass or less, and can be in the range of 20% by mass or less, based on the total amount (100% by mass) of the resin composition layer, and when used, is preferably in the range of 15% by mass or less. By setting the content in the above range, the adhesion can be suitably adjusted.

[0089] Examples of inorganic fillers include inorganic compounds such as silica, alumina, magnesium hydroxide, barium sulfate, calcium carbonate, antimony trioxide, magnesium oxide, zirconium oxide, talc, kaolinite, mica, basic magnesium carbonate, sericite, montmorolinite, bentonite, boron nitride, aluminum nitride, titanium nitride, etc. Among these, titanium nitride, silica, and zirconium oxide are preferred from the viewpoint of coating film resistance to scratches.

[0090] The curing accelerator may be contained in order to adjust the crosslinking rate of the resin composition layer of the present disclosure. The curing accelerator is not particularly limited and can be appropriately selected. Specific examples of the curing accelerator include amine-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators.

[0091] As described above, the encapsulating sheet of the present disclosure has a resin composition layer for forming an encapsulating layer sandwiched between a first film and a second film, and it is important that the surface roughness Ra of the resin composition layer on the surface in contact with the first film is 0.02 μm or more, and is preferably 60% or less of the thickness Ta of the resin composition layer. In addition, the cut level difference Rδc of the contour curve of the resin composition layer on the surface in contact with the first film is preferably 0.05 to 20 μm. The following methods can be used to obtain a resin composition layer having a surface roughness Ra and a cut level difference Rδc of a contour curve within such ranges. For example, a coating liquid of a resin composition for forming a resin composition layer is applied onto a second film, followed by drying, and the surface of the resin composition layer formed on the second film is covered with a first film having a predetermined surface shape, or a coating liquid of a resin composition for forming a resin composition layer is applied onto a first film having a predetermined surface shape, followed by drying, and the surface of the resin composition layer formed on the first film is covered with a second film to obtain an encapsulating sheet, and then, in a step prior to the step shown in FIG. 2(a), the first film is peeled off to invert and transfer the surface shape of the first film onto the surface of the resin composition layer. Another method is to prepare a mold with a predetermined surface shape separately, and press the mold against the surface of the resin composition layer formed on the second film, thereby inverting and transferring the predetermined surface shape to the surface of the resin composition layer. Alternatively, there can be mentioned a method in which fine particles or the like are collided with the surface of the resin composition layer formed on the second film, thereby directly forming the surface of the resin composition layer into a predetermined surface shape. The transfer method is preferred, preferably using a first film with a predetermined surface topography.

[0092] For coating, known coating machines and techniques such as a comma coater, a die coater, a roll coater, a lip coater, a reverse coater, a gravure coater, a bar coater, a curtain coater, dip coating, spin coating, silk screen, casting, etc. The solvent contained in the resin composition can be removed by a drying step after coating, and the amount of the solvent can be adjusted to adjust the viscosity of the coating liquid or the film thickness after drying. In a preferred embodiment, the resin composition is applied to a support such as a first film or a second film, and then the applied film is heated and dried using a hot air oven, an infrared heater, or the like to form a resin composition layer on one side of the support. Furthermore, in order to increase the crosslink density of the resin composition layer, it is preferable to perform an aging treatment such as leaving it to stand under specific temperature conditions, or to irradiate it with UV or the like. After coating, the resin composition may be transferred to another support such as a first film, a second film, or a substrate using a laminator.

[0093] [First Film] The first film is not particularly limited, and examples thereof include polyester films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, polyolefin films such as polypropylene and polyethylene, and plastic films such as polyvinyl chloride films, polyurethane films, nylon films, polyolefin films, triacetyl cellulose films, and cycloolefin films. From the viewpoint of handling, polyester films and polyolefin films are preferred.

[0094] The first film has a release layer on the surface facing the resin composition layer, which is preferably formed by applying a release agent such as a silicone resin, an alkyd resin, a fluororesin, or a melamine resin to the film, and from the viewpoint of handling (prevention of separation), a release layer using a silicone resin is more preferable. First film peeling force P l is preferably 0.1 to 15 gf / 20 mm, more preferably 0.3 to 10 gf / 20 mm, and further preferably 0.5 to 5 gf / 20 mm. First film peeling force P l can be adjusted by the release treatment of the release layer. For example, it can be adjusted by the type of release agent, the amount of release agent applied, and the surface roughness of the release layer. If it is desired to reduce the value of the release force, it is effective to treat the surface roughness to be rough or to increase the amount of release agent applied, and if it is desired to increase the value of the release force, it is only necessary to adjust in the opposite manner. First film peeling force P l can be measured, for example, by attaching the second film of the sealing sheet to a SUS plate and peeling the first film from the resin composition layer at a peel angle of 180° and a peel speed of 300 mm / min in an environment of 23° C. and relative humidity of 50%. The first film may have a functional layer in addition to the release layer, such as an antistatic layer or an antiblocking layer.

[0095] First film thickness T l In the case where a release layer or a functional layer is provided on the first film, the thickness T l is a value including the release layer and the functional layer. By setting the value in the above range, it is possible to prevent the waviness of the first film from being transferred to the resin composition layer, and to form a uniform resin composition layer. The first film is preferably one having a surface roughness Ra of 0.02 μm or more on the surface that is to come into contact with the resin composition layer, and 60% or less of the thickness Ta of the resin composition layer described below. When a first film having a surface roughness Ra of 0.02 μm or more is used and the surface roughness Ra is inverted and transferred to the surface of the resin composition layer, the resin composition layer is unlikely to be excessively attached to the surface of the micro LED during the process shown in FIG. 2(a), so that the placement position is easy to correct. Also, when a first film having a surface roughness Ra of 0.02 μm or more is used and the surface roughness Ra is inverted and transferred to the surface of the resin composition layer, air is unlikely to remain at the interface between the substrate and the resin composition layer during the process shown in FIG. 2(b), so that the appearance is good. That is, a resin composition layer having a surface roughness Ra of 0.02 μm or more is important in terms of blocking suppression and prevention, and air entrapment suppression and prevention, and is preferably 0.03 μm or more, more preferably 0.1 μm or more, and even more preferably 0.3 μm or more.

[0096] In addition, the surface roughness Ra of the surface of the resin composition layer is preferably large in terms of blocking suppression and prevention, and air entrapment suppression and prevention. On the other hand, in the process shown in FIG. 2(b), in terms of embedding property and smoothness for sufficiently filling the gaps between the micro LEDs and the periphery of the micro LEDs, it is preferable that the surface roughness Ra is not too large. When forming the resin composition layer by the transfer method, it is preferable to use a first film having a surface roughness Ra of 60% or less of the thickness Ta of the resin composition layer to be formed (before pressing), more preferably 50% or less, even more preferably 40% or less, and most preferably 20% or less.

[0097] The first film has a profile cut level difference Rδc of preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.5 μm or more on the surface to be in contact with the resin composition layer, and preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 6 μm or less.

[0098] [Second film] The second film is not particularly limited, and examples thereof include polyester films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, polyolefin films such as polypropylene and polyethylene, and plastic films such as polyvinyl chloride films, polyurethane films, nylon films, polyolefin films, triacetyl cellulose films, and cycloolefin films. From the viewpoint of handling, polyester films and polyolefin films are preferred. The second film is preferably laminated directly to the resin composition layer.

[0099] The second film preferably has a release layer on the surface facing the resin composition layer. The release layer is preferably formed by applying a release agent such as a silicone resin, an alkyd resin, a fluororesin, or a melamine resin to the film, and from the viewpoint of handling (prevention of tearing apart), a release layer using a silicone resin is more preferable. The peel strength P2 of the second film is preferably from 0.5 to 40 gf / 20 mm, more preferably from 0.8 to 30 gf / 20 mm, and even more preferably from 1.0 to 20 gf / 20 mm. The peeling force P2 of the second film can be adjusted by the release treatment of the release layer. For example, it can be adjusted by the type of release agent, the amount of release agent applied, and the surface roughness of the release layer. If you want to reduce the peeling force, it is effective to increase the surface roughness or the amount of release agent applied, and if you want to increase the peeling force, you can adjust it in the opposite way. The peel strength P2 of the second film is preferably greater than the peel strength P1 of the first film. The peel strength P2 of the second film can be measured, for example, by peeling the first film from the sealing sheet, attaching the exposed resin composition layer to a SUS plate, and then peeling the second film from the resin composition layer at a peel angle of 180° and a peel speed of 300 mm / min in an environment of 23°C and a relative humidity of 50%. The second film may have a functional layer other than the release layer, such as an antistatic layer or an antiblocking layer. The thickness T2 of the second film is 12 to 188 μm, more preferably 12 to 100 μm, and further preferably 20 to 60 μm. When a release layer or a functional layer is provided on the second film, the thickness T2 is a value including the release layer and the functional layer. By setting the thickness within the above range, the pressure transmission applied to the resin composition layer in the pressing step described below is controlled, and the resin composition layer flows uniformly, resulting in good embeddability and adhesion. EXAMPLES

[0100] The present disclosure will be specifically described below with reference to examples and comparative examples, but the present disclosure is not particularly limited to the examples. In the following description, "parts" and "%" represent "parts by mass" and "% by mass", respectively, unless otherwise specified.

[0101] Weight average molecular weight (Mw), solid content, thickness, loss modulus (G'' 100 The numerical values ​​obtained in this embodiment, such as those shown above, were obtained by the following method.

[0102] [Weight average molecular weight (Mw)] The weight average molecular weight (Mw) was measured using a GPC "LC-GPC system" manufactured by Shimadzu Corporation, and was calculated by conversion using polystyrene with a known molecular weight as a standard substance. Device name: Shimadzu Corporation, LC-GPC system "Prominence" Column: Four GMHXL columns manufactured by Tosoh Corporation and one HXL-H column manufactured by Tosoh Corporation were connected together. Mobile phase solvent: Tetrahydrofuran Flow rate: 1.0mL / min Column temperature: 40℃

[0103] [Solid content] The mass of the aluminum cup (W0) was measured using a precision balance. Next, about 1 g of sample was placed in the aluminum cup, and the mass of the sample in the aluminum cup (W1) was measured using a precision balance. The sample in the aluminum cup was heated in an oven at 150°C for 120 minutes, then removed from the oven and returned to room temperature. The residual mass (W2) of the sample in the aluminum cup after heating was measured using a precision balance. The solid content was then calculated using the formula (W2-W0) / (W1-W0)×100(%).

[0104] [Thickness of encapsulating sheet T t , the thickness T of the resin composition layer a , thickness of the first film T1, thickness of the second film T2] The encapsulating sheet is cut to a size of 10 cm x 10 cm. Ten equally spaced points are determined from one end to the other end in the width direction, and the thickness of the ten points is measured. The average value is the thickness T of the encapsulating sheet. t Next, the first film was peeled off from the sealing sheet, and the thickness of the peeled first film was measured at 10 positions corresponding to the same positions as above. The average value was taken as T1. Thereafter, the second film was further peeled off from the resin composition layer, and the thickness of the peeled second film was measured at 10 positions corresponding to the same positions as above. The average value was taken as T2. The thickness T of the resin composition layer a is T a =T t The thickness was measured using a MH-15M (Nikon Corporation).

[0105] [Tg of resin composition layer, loss modulus (G'') at 100°C 100 ) and loss tangent (tan δ 100 )] Two sets of sheets from which the first release sheet of the sealing sheet had been peeled off were prepared, and the adhesive layers were bonded together using a laminator set at 90°C to prepare a laminate of second release sheet / resin composition layer / second release sheet. The second release sheet on one side of this laminate was peeled off, and the resin composition layers were sequentially bonded together to form a resin composition layer having a thickness of 1 mm. The loss modulus (G'') and loss tangent (tanδ) of this resin composition layer were measured using a rheometer (manufactured by TA Instruments, DHR-2) with a φ8 mm measurement probe under conditions of a strain of 0.1%, a frequency of 1 Hz, and a heating rate of 3°C / min from -50°C to 150°C. The temperature at the peak top of the loss tangent (tan δ) was taken as Tg. If multiple peak tops were obtained, the highest peak top was taken as Tg. In addition, the measured values ​​of loss modulus (G'') and loss tangent (tan δ) at a temperature of 100°C were read from the obtained data.

[0106] [Surface roughness Ra, cutting level difference of profile curve Rδc] The surface roughness Ra defined in the present invention is obtained by extracting a portion of the roughness curve with a measurement length L in the direction of its center line, and calculating the arithmetic average of the absolute values ​​of the deviation between the center line of this extracted portion and the roughness curve. The cut level difference Rδc of the profile curve is the difference in the height direction levels that correspond to any two load length ratios in the roughness curve, and in the present invention, the two load length ratios are defined as 25% and 75%. In this disclosure, the surface roughness Ra and the cut level difference Rδc of the contour curve are both values ​​measured in accordance with JIS B0601: 2013. Specifically, measurement data is acquired using a laser microscope (VK-X100, manufactured by Keyence Corporation), the acquired measurement data is imported into analysis software (analysis application "VK-H1XA" equipped with JIS B0601: 2013 surface texture measurement module "VK-H1XR", both manufactured by Keyence Corporation), and the JIS B0601: 2013 surface texture measurement is performed to perform the calculation. In the present disclosure, in order to obtain a roughness curve from a measured cross-sectional curve obtained by measurement, a λc profile filter that removes short wavelengths such as noise and a λs profile filter that removes long wavelengths of waviness were used. Depending on the surface condition to be measured, either a λs profile filter of 2.5 μm, a λc profile filter of 0.8 mm, a λs profile filter of 8 μm, a λc profile filter of 2.5 mm, or a λs profile filter of 25 μm, a λc profile filter of 8 mm was selected in the surface roughness measurement of the analysis application to measure the surface roughness Ra and the cut level difference Rδc of the profile.

[0107] <Production and preparation of resin (A)> [Preparation of (meth)acrylic resin (a1-1) solution] A reaction vessel (hereinafter simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping device, and a nitrogen inlet tube was charged with 80 parts of ethyl acetate, 41 parts of methyl methacrylate, 58 parts of n-butyl methacrylate, 1 part of 4-hydroxybutyl acrylate, and 0.1 parts of 2,2'-azobisisobutyronitrile as an initiator, and the atmosphere in the reaction vessel was replaced with nitrogen gas. Then, the mixture was heated to 75°C while stirring under a nitrogen atmosphere to start the reaction. The reaction solution was then reacted at 75°C for 4 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain a solution of (meth)acrylic resin (a1-1) having a weight average molecular weight (Mw): 100,000 and a solid content: about 25% and having a hydroxyl group.

[0108] [Production Example of (Meth)acrylic Resin (a1-2) Solution] After obtaining a solution of (meth)acrylic resin (a1-1), an equivalent amount of Karenz AOI (2-acryloyloxyethyl isocyanate, manufactured by Resonac Corporation) corresponding to half the amount of hydroxyl groups of the 4-hydroxybutyl acrylate used in the copolymerization was added as a modifier, and the mixture was stirred at 60°C for 24 hours. If necessary, the mixture was diluted with ethyl acetate to obtain a solution of (meth)acrylic resin (a1-2) having hydroxyl groups and methacryloyl groups (solid content: approximately 25%).

[0109] [Preparation of solution of (meth)acrylic resin (a1-3)] According to the monomer composition shown in Table 1, a solution of (meth)acrylic resin (a1-3) having a hydroxyl group with a weight average molecular weight (Mw) of 100,000 and a solid content of approximately 25% was obtained in the same manner as in the case of the solution of (meth)acrylic resin (a1-1).

[0110] [Production Example of (Meth)acrylic Resin (a1-4) Solution] After obtaining a solution of (meth)acrylic resin (a1-3), an equivalent amount of Karenz AOI (2-acryloyloxyethyl isocyanate, manufactured by Resonac Corporation) corresponding to half the amount of hydroxyl groups of the 4-hydroxybutyl acrylate used in the copolymerization was added as a modifier, and the mixture was stirred at 60°C for 24 hours. If necessary, the mixture was diluted with ethyl acetate to obtain a solution of (meth)acrylic resin (a1-4) having hydroxyl groups and methacryloyl groups (solid content: approximately 25%).

[0111] [Production Examples of Solutions of (Meth)acrylic Resins (a1-5) to (a1-10)] Using the monomer compositions and modifiers shown in Table 1, solutions of (meth)acrylic resins (a1-5) to (a1-10) having hydroxyl groups and methacryloyl groups (solid content: approximately 25%) were obtained in the same manner as for the solution of (meth)acrylic resin (a1-4).

[0112] [Production Example of (Meth)acrylic Resin (a1-11) Solution] As shown in Table 1, the amounts of monomers blended were 14 parts of n-butyl acrylate, 84 parts of n-butyl methacrylate, and 2 parts of acrylic acid, and a solution of (meth)acrylic resin (a1-11) having a carboxy group and having a weight average molecular weight (Mw) of 100,000 and a solid content of approximately 25% was obtained by the same method as in the production of (meth)acrylic resin (a1-1).

[0113] [Production Example of (Meth)acrylic Resin (a1-12) Solution] After obtaining a solution of (meth)acrylic resin (a1-11), an equivalent amount of glycidyl methacrylate corresponding to half the amount of the carboxy groups of the acrylic acid subjected to copolymerization was added, and the mixture was stirred at 60°C for 24 hours, and diluted with ethyl acetate as necessary to obtain a solution of (meth)acrylic resin (a1-12) having carboxy groups and methacryloyl groups (solid content: approximately 25%).

[0114] [Production Examples of (Meth)acrylic Resin (a1-13) to (a1-15) Solutions] Using the monomer compositions and modifiers shown in Table 1, solutions of (meth)acrylic resins (a1-13) to (a1-15) having carboxy groups and methacryloyl groups (solid content: approximately 25%) were obtained in the same manner as for the solution of (meth)acrylic resin (a1-12).

[0115] [Table 1]

[0116] The symbols in the table are as follows: MMA: Methyl methacrylate nBMA: n-butyl methacrylate nBA: n-butyl acrylate iBMA: i-butyl methacrylate 4HBA: 4-hydroxybutyl acrylate 2HEA: 2-hydroxyethyl acrylate AA: Acrylic acid GMA: glycidyl methacrylate

[0117] [Example of preparation of urethane resin (a2) solution] A solution (solid content: about 25%) of polyurethane resin "VA-9320" (manufactured by Toyochem Co., Ltd.) with an acid value of 10 mgKOH / g was prepared.

[0118] [Example of preparation of epoxy resin (a3) ​​solution] Teisan Resin SG-80H (manufactured by Nagase Chemtex Corporation) having a weight average molecular weight (Mw) of 350,000 was diluted with ethyl acetate to prepare a solution of epoxy resin (a3) ​​having a solid content of about 25%.

[0119] [Example 1] <Production of Liquid Resin Composition for Forming Sealing Layer> 380 parts of a solution containing 95 parts of the above-mentioned (meth)acrylic resin (a1-2) as resin (A) and 5 parts of (B-1) di-t-amyl peroxide (Luperox DTA, manufactured by Arkema Yoshitomi Co., Ltd.) as a polymerization initiator were stirred in a disperser, and then filtered through a membrane filter having a pore size of 10 μm to remove coarse foreign matter that may cause coating unevenness, thereby obtaining a liquid resin composition 1.

[0120] <Production of encapsulating sheets> The liquid resin composition 1 was applied onto the release layer of a 50 μm-thick second film, SP-PET-O3-BU (manufactured by Mitsui Chemicals Tocello), so that the thickness after drying would be 30 μm, and the applied film was dried in a hot air oven at 100°C for 3 minutes to form a resin composition layer. Next, the release layer side of Cosmo Peel E7001 (manufactured by Toyobo Co., Ltd.) having a thickness of 50 μm, a surface roughness Ra of 0.04 μm on the release layer side, and an Rδc of 0.06 μm was bonded to the exposed resin composition layer, and aged at 4° C. for 7 days to obtain a transparent encapsulating sheet of Example 1 laminated in the order of first film / transparent resin composition layer / second film, which was evaluated according to the method described below. The surface of the resin composition layer exposed by peeling off the first film had a surface roughness Ra of 0.06 μm and Rδc of 0.09 μm. In addition, the Tg of the resin composition layer in the produced encapsulating sheet was 75° C., tanδ 100 is 0.91, G'' 100 is 3.2 x 10 5 It was Pa.

[0121] [Examples 2 to 8], [Comparative Example 1] As shown in Table 2, encapsulating sheets were produced and evaluated in the same manner as in Example 1, except that the following films were used as the first film. Note that the resin composition for forming the encapsulating layer shown in Table 2 indicates the solid content. KOBATECH RF 40TLGN (manufactured by Kobayashi), thickness 40μm, Ra: 0.14μm, Rδc: 0.21μm KOBATECH RF 40TLSN (manufactured by Kobayashi), thickness 40μm, Ra: 0.31μm, Rδc: 0.50μm KOBATECH RF 40TLMN (manufactured by Kobayashi), thickness 40μm, Ra: 1.10μm, Rδc: 1.52μm Cosmo Peel E7002 (manufactured by Toyobo Co., Ltd.), thickness 50 μm, Ra: 0.01 μm, Rδc: 0.03 μm PG7H (manufactured by Godo Resin Industries Co., Ltd.), thickness 50 μm, Ra: 2.73 μm, Rδc: 4.41 μm PG15H (manufactured by Godo Resin Industries Co., Ltd.), thickness 50μm, Ra: 3.80μm, Rδc: 6.29μm PG12H (manufactured by Godo Resin Industries Co., Ltd.), thickness 50 μm, Ra: 10.49 μm, Rδc: 14.31 μm

[0122] [Examples 9 to 38], [Comparative Examples 2 to 3] Except for changing the resin (A), the initiator (B), the crosslinking agent (E), and the first film as shown in Tables 3 to 5, an encapsulating sheet was produced in the same manner as in Example 1, and was evaluated in the same manner. It should be noted that Example 10 in Table 3 is a re-recording of Example 1, and Example 19 in Table 4 is a re-recording of Example 4.

[0123] [Examples 39 to 41] As shown in Table 6, PG12H (manufactured by Godo Resin Industries Co., Ltd.) was used as the first film, the same coating liquid as in Example 11 was used as the resin composition for forming the sealing layer, and the thickness of the resin composition layer for forming the sealing layer was 100 μm, 50 μm, or 30 μm. Except for this, sealing sheets were obtained in the same manner as in Example 1 and evaluated in the same manner.

[0124] The abbreviations in the table are as follows. <Polymerization initiator (B)> (B-1): Di-t-amyl peroxide (Luperox DTA, manufactured by Arkema Yoshitomi Co., Ltd.) (B-2): 2,2'-azobis(N-butyl-2-methylpropionamide) (Vam-110, Fujifilm Wako Pure Chemical Industries, Ltd.) <Crosslinking agent (E)> (E-1): Isocyanate compound (Cosmonate T100, manufactured by Mitsui Fine Chemicals) (E-2): Aziridine compound (Chemitite PZ-33, manufactured by Nippon Shokubai Co., Ltd.) (E-3): Dicyandiamide compound (jER Cure DICY8, manufactured by Mitsubishi Chemical Corporation)

[0125] [Table 2]

[0126] [Table 3]

[0127] [Table 4]

[0128] [Table 5]

[0129] [Table 6]

[0130] <Preparation of Dispersion (D) of Colorant (C)> [Production Example of Dispersion (D-1) of Colorant (C)] 2,400 parts of resin (a1-12) solution (solid content approximately 25%), 800 parts of (C-1) carbon black MA100 (manufactured by Mitsubishi Chemical Corporation) as a colorant, and 800 parts of methyl ethyl ketone (hereinafter referred to as MEK) as a dispersion medium were mixed and pre-dispersed using a disperser. After that, the main dispersion was carried out for 2 hours using a 0.6 L Dyno Mill filled with 1,800 g of zirconia beads with a diameter of 1.0 mm, to obtain a dispersion (D-1) with a solid content of approximately 35%.

[0131] [Production Examples of Dispersions (D-2) to (D-4) of Colorant (C)] Dispersions (D-2) to (D-4) with solid contents of approximately 35% were obtained in the same manner as for dispersion (D-1), except that 2,400 parts each of the solution of resin (a1-13), the solution of resin (a1-14), and the solution of resin (a1-15) were used instead of 2,400 parts of the solution of resin (a1-12).

[0132] [Production Example of Dispersion (D-5) of Colorant (C)] A dispersion (D-5) with a solid content of approximately 35% was obtained in the same manner as for dispersion (D-1), except that (C-2) metal oxide pigment Black 6340 (manufactured by Asahi Chemical Industry Co., Ltd.) was used as the colorant instead of (C-1).

[0133] [Production Example of Dispersion (D-6) of Colorant (C)] Dispersion (D-6) with a solid content of approximately 35% was obtained in the same manner as dispersion (D-1), except that (C-3) metal oxide pigment Typeque CR-97 (manufactured by Ishihara Sangyo Kaisha) was used as the colorant instead of (C-1).

[0134] [Example 101] <Production of liquid black resin composition for forming black sealing layer> 240 parts of a solution containing 60 parts of resin (a1-12), 100 parts of a dispersion (D-1) containing 20 parts of colorant (C-1), 15 parts of resin (a1-12), and 65 parts of a dispersion medium, and 5 parts of a polymerization initiator (B-1) di-t-amyl peroxide were stirred in a disperser, and then filtered through a membrane filter having a pore size of 10 μm to remove coarse foreign matter that may cause coating unevenness, thereby obtaining a liquid resin composition 101.

[0135] <Production of black encapsulating sheet> An encapsulating sheet was obtained in the same manner as in Example 1, except that the liquid black resin composition 101 was used instead of the liquid resin composition 1 used in Example 1, and was evaluated in the same manner.

[0136] [Examples 102 to 108], [Comparative Example 101] As in the cases of Examples 1 to 8 and Comparative Example 1, except that the first film was changed as shown in Table 7, an encapsulating sheet was obtained in the same manner as in Example 101, and was evaluated in the same manner.

[0137] [Examples 109 to 122] An encapsulating sheet was prepared in the same manner as in Example 101, except that the resin (A), dispersion (D), initiator (B), crosslinking agent (E), and first film were changed as shown in Tables 8 to 9, and evaluated in the same manner. In addition, Example 110 in Table 8 is a re-recording of Example 101, and Example 117 in Table 9 is a re-recording of Example 104.

[0138] [Examples 123 to 125] As shown in Table 10, PG12H (manufactured by Godo Resin Industries Co., Ltd.) was used as the first film, a coating liquid containing resin (a1-15) / colorant (C-1) / initiator (B-1) = 75 / 20 / 5 (parts by mass) was used as the resin composition for forming the sealing layer, and the thickness of the resin composition layer for forming the sealing layer was 100 μm, 50 μm, or 30 μm. Except for this, a sealing sheet was obtained in the same manner as in Example 101 and evaluated in the same manner.

[0139] [Table 7]

[0140] [Table 8]

[0141] [Table 9]

[0142] [Table 10]

[0143] [evaluation] <Blocking resistance> As shown in FIG. 5(a), two metal rods 9 each measuring 20 mm×20 mm×60 mm were attached in parallel to a metal plate 8 measuring 100 mm×100 mm×1 mm with a gap of 25 mm between them using double-sided adhesive tape (not shown). The encapsulating sheet was cut to a size of 50 mm×50 mm, and the first film was peeled off to expose the resin composition layer, thereby obtaining a laminate 2′ of the second film and the resin composition layer. As shown in Figure 5 (b), the laminate 2' was rolled up and inserted between metal rods 9 attached in parallel to a metal plate 8 with the resin composition layer facing upward, so that the top of the upper surface of the laminate 2' was higher than the two metal rods 9, and placed so that both ends of the laminate 2' were in contact with the upper surface of the metal plate 8. Thereafter, as shown in Fig. 5(c), a glass plate 10 having a size of 80 mm x 80 mm was placed so as to be in contact with the resin composition layer and the upper surfaces of the two metal rods 9. Fig. 5(d) is a schematic diagram of the placed state as viewed from the glass plate 10 side. The resin composition layer was visually observed from the outside of the placed glass plate 10 (the upper part of FIG. 5(c)), and blocking resistance was evaluated based on the presence or absence of interference fringes. ◯: No interference fringes were observed. ×: Interference fringes were observed.

[0144] <Air release> A glass plate measuring 200 mm x 120 mm was prepared. The sealing sheet was cut to a size of 200 mm x 120 mm, the first film was peeled off to expose the resin composition layer, and the resin composition layer was placed on the first surface of the glass plate. Then, on the second film, a 50 μm thick TPX (Opulant X-44B, manufactured by Mitsui Chemicals Tocello Co., Ltd.) and a 2 mm thick PVC film (Celeb T, manufactured by Okamoto Co., Ltd.) were placed in order as cushioning materials, and cardboard was placed to prevent adhesion. The laminate consisting of glass plate / resin composition layer / second film / cushioning material (TPX / PVC film) / cardboard was pressed from above against the substrate surface under conditions of 3 MPa and 100° C. for 10 minutes, and the resin composition layer was adhered to the glass plate. After pressing, the cushioning material and the cardboard were peeled off. An arbitrary 80 mm x 80 mm area was visually observed from the second surface side of the obtained sealing layer and the glass plate with the second film, and the air escape property was evaluated based on the maximum diameter of the poor adhesion area occurring at the interface between the resin composition layer and the glass plate. ◎: The maximum diameter of the gap is less than 3 mm. ○: The maximum diameter of the gap is 3mm or more and less than 10mm. △: The maximum diameter of the gap is 10 mm or more and less than 20 mm. ×: The maximum diameter of the gap is less than 20 mm.

[0145] <Smoothness> For the sealing layer and the glass plate with the second film used in the air release property evaluation, a laser microscope was used from the glass plate side to observe extremely small voids at the interface between the glass plate and the resin composition layer. The smoothness of the interface between the resin composition layer and the glass plate was evaluated by calculating the surface roughness Ra value using the value measured in accordance with JIS B0601:2013. ◎: Surface roughness Ra is less than 0.02 μm. ◯: Surface roughness Ra is 0.02 μm or more and less than 0.1 μm. △: Surface roughness Ra is 0.1 μm or more and less than 0.5 μm. ×: Surface roughness Ra is 0.5 μm or more.

[0146] <Embeddability> A test substrate was prepared that mimicked the unevenness of a micro LED substrate (a glass plate measuring 25 mm × 25 mm, with multiple depressions of 200 μm wide, protrusions of 5 μm high, and protrusions of 200 μm wide formed in a checkerboard pattern on one side). A schematic cross-sectional view of the test substrate is shown in Figure 3. The sealing sheet was cut to a size of 30 mm x 30 mm, the first film was peeled off to expose the resin composition layer, and the resin composition layer was placed on the surface of the test substrate on which the uneven portion was formed. Thereafter, a 50 μm thick TPX (Opulant X-44B, manufactured by Mitsui Chemicals Tocello Co., Ltd.) and a 2 mm thick PVC film (Celeb T, manufactured by Okamoto Co., Ltd.) were placed on the second film as cushioning materials in that order, and cardboard was placed on top to prevent sticking. A laminate consisting of a glass substrate / resin composition layer / second film / cushioning material (TPX / PVC film) / cardboard was pressed against the substrate surface from above at 3 MPa and 100° C. for 10 minutes, and the resin composition layer was filled in the recesses of the test substrate to form a sealing layer. After pressing, the cushioning material and the cardboard were peeled off. Four corners of 15 random recesses (60 locations in total) of the obtained test substrate with the sealing layer and second film were observed from the glass plate side with a microscope, and the embeddability was evaluated based on the number of locations where gaps occurred. ◎: More than 56 locations with no gaps. ○: There are 41 or more and 55 or less places with no gaps. △: 29 or more and 40 or less recesses without gaps. ×: 28 or less recesses without gaps. [Explanation of symbols]

[0147] 1: Encapsulating sheet 2: Resin composition layer 2': Laminate (the first film 3 is peeled off from the sealing sheet 1) 3: First film 4: Second film 5: Light emitting element 6: Substrate 7: Glass substrate 8:Metal plate 9: Metal rod 10: Glass plate

Claims

1. A sealing sheet for sealing between micro LED elements for a display using a plurality of micro LED elements as a light source, The encapsulating sheet includes a first film, a resin composition layer for forming an encapsulating layer, and a second film arranged in this order, The surface roughness Ra of the resin composition layer on the surface in contact with the first film is 0.02 μm or more, The resin composition layer has a glass transition temperature of 20° C. or higher and a loss tangent (tanδ) at 100° C., which is measured by dynamic viscoelasticity measurement in a torsion mode at a frequency of 1 Hz. 100 ) is 0.2 or more; Sealing sheet.

2. Loss tangent at 100°C (tan δ 100 2. The encapsulating sheet according to claim 1, wherein the tensile strength (T) is 2.5 or less.

3. The encapsulating sheet according to claim 1 or 2, wherein a cut level difference Rδc of a contour curve of the resin composition layer on a surface in contact with the first film is 0.05 to 20 μm.

4. The loss modulus (G″) at 100° C. obtained by dynamic viscoelasticity measurement at a frequency of 1 Hz of the resin composition layer 100 ) is 5 x 10 3 Pa ~ 2 x 10 7 The encapsulating sheet according to claim 3 .

5. The encapsulating sheet according to claim 4, wherein the resin composition layer has a thickness Ta of 1 to 100 μm.

6. A display panel having an encapsulating layer comprising the resin composition layer of the encapsulating sheet according to claim 1 or 2.

7. A method for manufacturing a display panel, comprising the following steps (1) to (6). (1) A step of preparing the encapsulating sheet according to claim 1 or 2, in which a first film, a resin composition layer for forming an encapsulating layer, and a second film are arranged in this order; (2) preparing an object to be sealed, the object being a substrate having a plurality of micro LED elements arranged at intervals on one surface of the substrate; (3) peeling off the first film from the encapsulating sheet to expose the resin composition layer for forming an encapsulating layer; (4) contacting the exposed resin composition layer for forming an encapsulating layer with the light emitting surfaces of the micro LED elements; (5) filling a resin composition layer for forming an encapsulating layer between the plurality of micro LED elements; (6) Peeling off the second film.

Citation Information

Patent Citations

  • Thermal crosslinking sheet, solar cell module, and laminate

    JP2014022455A

  • Element-sealing transparent resin composition for organic electronic devices, element-sealing resin sheet for organic electronic devices, organic electroluminescent element, and image display

    JP2015191800A

  • Sealing sheet for electronic device and manufacturing method for electronic device package

    JP2017098353A

  • Sheet for sealing optical semiconductor element

    JP2021163963A

  • Sealing-resin sheet

    JP2021197497A